Bypassing stroke-damaged neural pathways via a neural interface induces targeted cortical adaptation - Kenji Kato (Nature Portfolio, 2019)
Monkeys were trained to use an artificial cortico-muscular connection (ACMC) to regain control over a paralyzed hand following subcortical stroke. Control over the paralyzed hand was accompanied by the appearance of localized high-gamma modulation in the cortex, which could be rapidly reset and relocalized to a different cortical site to reactivate motor control.